2021
DOI: 10.1111/1541-4337.12881
|View full text |Cite
|
Sign up to set email alerts
|

Tetrodotoxin in live bivalve mollusks from Europe: Is it to be considered an emerging concern for food safety?

Abstract: Tetrodotoxins (TTXs) are a group of potent neurotoxins named after the Tetraodontidae fish family (pufferfish). TTXs have been reported in several animal taxa, both terrestrial and marine. The ingestion of TTX‐contaminated flesh can cause serious neurotoxic symptomatology and can eventually lead to death. Traditionally, TTXs have been associated with Asian countries, in particular with pufferfish consumption. However, they have also been reported in bivalve mollusks farmed in the Pacific area and, recently, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 111 publications
(219 reference statements)
0
8
0
Order By: Relevance
“…Method sensitivities, as quantified by LOD and LOQ, varied enormously, but such data is hard to standardize for MS/MS detection methods, given the notable variation in the algorithms utilized by instrument software for calculating S/N. Notably, LODs quoted by participants in this study were higher than those reported by four previous SLV studies ( 36 , 39 , 40 , 45 ). However, other than the initial validation which was targeting quantitation of TTX at a higher order of magnitude in sea slugs [mg/kg ( 23 )], all methods published and/or utilized in this study are capable of quantifying at concentrations well below the EFSA recommended threshold of 44 µg/kg ( Table 8 ) and consequently are appropriate for regulatory control purposes.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…Method sensitivities, as quantified by LOD and LOQ, varied enormously, but such data is hard to standardize for MS/MS detection methods, given the notable variation in the algorithms utilized by instrument software for calculating S/N. Notably, LODs quoted by participants in this study were higher than those reported by four previous SLV studies ( 36 , 39 , 40 , 45 ). However, other than the initial validation which was targeting quantitation of TTX at a higher order of magnitude in sea slugs [mg/kg ( 23 )], all methods published and/or utilized in this study are capable of quantifying at concentrations well below the EFSA recommended threshold of 44 µg/kg ( Table 8 ) and consequently are appropriate for regulatory control purposes.…”
Section: Resultsmentioning
confidence: 62%
“…Whilst numerous reports of TTX in seafood products have been published in recent years using LC–MS/MS, a relatively low number of these methods have been subjected to full validation studies. Table 8 summarizes the main method performance characteristics from this study in comparison with those determined in published LC–MS/MS validation studies to date ( 23 , 34 , 36 , 39–41 , 45 ) together with the performance characteristics for the ELISA method ( 46 ) and a comparative biosensor method ( 52 ). Previous LC–MS/MS single-laboratory validations (SLVs) have demonstrated recoveries which are generally good, ranging from 61 to 121% on average.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TTX poisoning in humans used to be associated with puffer fish consumption, and most intoxications were limited to East Asia because of the food culture there [ 6 ]. In recent years, however, TTX has been found in other species, such as bivalves and gastropods, which are important sources of animal protein food in coastal areas [ 7 , 8 ]. Its geographical distribution has expanded to various regions of the Mediterranean Sea, and the Pacific and Indian Oceans [ 1 ].…”
Section: Introductionmentioning
confidence: 99%